2022
DOI: 10.1111/1744-9987.13858
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of the Turkish version of the Shortened Xerostomia Inventory in hemodialysis patients

Abstract: Introduction:The aim of this study was to translate, linguistically validate, and evaluate the psychometric properties of the Shortened Xerostomia Inventory (SXI) among Turkish patients undergoing hemodialysis (HD). Methods:The study was conducted with 81 chronic HD patients in the HD units of two state hospitals between June and August 2020. Explanatory factor analysis was implemented to test the construct validity. In addition, the testretest method was performed to test the reliability and consistency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
3
1
0
Order By: Relevance
“…As the factor loading value of each item exceeded 0.70, it was confirmed that the items had good internal consistency to properly measure xerostomia [28]. The results of EFA in this study were consistent with translated versions of SXI, such as Chinese [12] and Turkish [26] versions. On the other hand, in the CFA, some goodness-of-fit indices of the single factor model were found to be unsuitable, which differed from the previous study [12].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…As the factor loading value of each item exceeded 0.70, it was confirmed that the items had good internal consistency to properly measure xerostomia [28]. The results of EFA in this study were consistent with translated versions of SXI, such as Chinese [12] and Turkish [26] versions. On the other hand, in the CFA, some goodness-of-fit indices of the single factor model were found to be unsuitable, which differed from the previous study [12].…”
Section: Discussionsupporting
confidence: 81%
“…Despite the limitation of a longer interval before the retest, the ICC value was 0.90, which was confirmed to be an excellent degree of agreement [25]. The ICCs of SXI translation studies in other countries have ranged from 0.90 to 0.99 [17,26]. The mean age of the participants in this study was 89 years old.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations